A Pilot Study on the Association of Mitochondrial Oxygen Metabolism and Gas Exchange During Cardiopulmonary Exercise Testing: Is There a Mitochondrial Threshold? - Baumbach, Philipp; Schmidt-Winter, Christiane; Hoefer, Jan; Derlien, Steffen; Best, Norman; Herbsleb, Marco; Coldewey, Sina M. (Frontiers in Medicine, 2020)
BACKGROUND: Mitochondria are the key players in aerobic energy generation via oxidative phosphorylation. Consequently, mitochondrial function has implications on physical performance in health and disease ranging from high performance sports to critical illness. The protoporphyrin IX-triplet state lifetime technique (PpIX-TSLT) allows in vivo measurements of mitochondrial oxygen tension (mitoPO2). Hitherto, few data exist on the relation of mitochondrial oxygen metabolism and ergospirometry-derived variables during physical performance. This study investigates the association of mitochondrial oxygen metabolism with gas exchange and blood gas analysis variables assessed during cardiopulmonary exercise testing (CPET) in aerobic and anaerobic metabolic phases. METHODS: 17 volunteers underwent an exhaustive CPET (graded multistage protocol, 50W/5 min increase), of which 14 were included in the analysis. At baseline and for every load level PpIX-TSLT-derived mitoPO2 measurements were performed every 10 seconds with 1 intermediate dynamic measurement to obtain mitochondrial oxygen consumption and delivery (mitoV̇O2, mitoḊO2). In addition, variables of gas exchange and capillary blood gas analyses were obtained to determine ventilatory and lactate thresholds (VT, LT). Metabolic phases were defined in relation to VT1 and VT2 (aerobic: